2018
DOI: 10.1111/imj.13620
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory reporting by doctors of medically unsafe drivers is unpopular and poorly adhered to: a survey of sleep physicians and electro‐physicians

Abstract: Widely disliked and causing deterioration of doctor-patient relationships, the MR law is ignored by some and inconsistently applied by most of the doctors surveyed. Further clinician and community education is required regardless of whether the law is abandoned, modified or left unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Systematic review findings (now published: Koppel, et.al, 2019) identified that mandatory reporting increases MP FTD awareness but impacts negatively on doctor-patient relationships and public health (e.g. drivers not seeking treatment for fear of reporting/licence loss, Elgar & Smith, 2018).…”
Section: Results and Knowledge Translation Outputsmentioning
confidence: 99%
“…Systematic review findings (now published: Koppel, et.al, 2019) identified that mandatory reporting increases MP FTD awareness but impacts negatively on doctor-patient relationships and public health (e.g. drivers not seeking treatment for fear of reporting/licence loss, Elgar & Smith, 2018).…”
Section: Results and Knowledge Translation Outputsmentioning
confidence: 99%